Estimated enteric methane production from volatile fatty acids in the ruminal fluid of dairy cows supplemented with Lithothamnium Calcareum (Revista de Ciências Agroveterinárias, 2024)
The aim of this study was to estimate methane (CH4) production from the proportions of volatile fatty acids (VFA) in ruminal fluid and to determine its relationship with dry matter intake (DMI) in dairy cows supplemented with Lithothamnium calcareum. Six multiparous lactating Holstein cows were divided into two experimental groups: control group (CON; n=3) supplemented with 1.1% DM of sodium bicarbonate; and Lithothamnium calcareum group (LITHO; n=3) supplemented with 0.5% DM of Lithothamnium calcareum. Ruminal fluid was collected once a week to evaluate pH and VFA. DMI of the animals was recorded daily. CH4 production was estimated using equations based on ruminal VFA proportions. There was no difference in DMI (kg/day), VFA concentrations and acetate/propionate ratio between the groups (P>0.05). The methane yield (g CH4/kg DMI) did not differ (P>0.05) between the groups in the equation models tested. There was no satisfactory correlation between DMI and CH4 yield for animals in the LITHO and CON groups. Lithothamnium calcareum as a feed additive was not able to reduce CH4 production, estimated from equations based on ruminal VFA proportions.
Keywords: methane mitigation; seaweed; ruminants; greenhouse gas